Visual effects as a part of effective storytelling - Mohammad Firdaus, Hassan (Universiti Malaysia Sarawak (UNIMAS), 2016)
The advancement in technology enables a much more powerful computer which results in widespread uses of visual effects. Nowadays, we can see many filmmakers are using visual effects as a part of their film. The use of visual effects had been a common practice nowadays and much more advance if we compare from decades ago. These comes a problem when visual effects are everywhere but the narrative of the films becomes forgetful. The audience are amaze by its visual appeal but will forget the film in just a few weeks. The researcher questions if there is a way where the filmmakers can implements visual effects in their films without eroding the narrative of the film.